Future Direction of Identity Research in a Context of Political Struggle: A Critical Appraisal of Erikson. Issue 4 (2nd October 2018) - Alberts, Charl; Durrheim, Kevin
ABSTRACT: Identity research has become a prominent field of study in the social sciences, but the conceptualization and measurement of the construct of identity remains contested. Although Erikson's theoretical work has been extremely influential in directing theory and research over the past 50 years, the theory has elicited a variety of criticisms. In this article, we critically reflect on the application of Erikson's theory in contexts of social and political struggle. We engage with Eriksonian theory in terms of the debate regarding the relationship between society and the individual. We develop a view of identities as historically contingent contextual discursive performances. Empirical material from two South African studies is presented to illustrate our argument about how the sociopolitical context of struggle and threat shapes and structures the identity aspirations and decisions of young people.